Uji Kuat Tekan Beton dengan Menggunakan Pasir Kali Desa Rongi Kec. Sampolawa Kab. Buton Selatan - Muh. Sayfullah S; Musrifin Musrifin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2020)
This study aims to determine the characteristics of fine aggregate material characteristics originating from Rongi Village, Sampolawa Subdistrict, coarse aggregate originating from Badene Village, Batauga Subdistrict, and to determine the compressive strength produced by concrete against the mixture of materials using fine aggregate originating from Rongi Village and coarse aggregate comes from the Badene Village of Batauga District. In this study the material was mixed using water with a cement water factor of 0.59. The compressive strength test is carried out at the age of 3 days, 7 days and 28 days, with a slinder size of 15cm x 30cm. The sample of specimens in this study amounted to 15 pieces. From the results of tests carried out the compressive strength value of the concrete produced using fine aggregate material derived from Rongi Village and coarse aggregate originating from the Village of Sangatene that is an average at 3 days of 94.5 kg / cm2, age 7 days is 119.6 kg / Cm2, and age 28 days is 192.5 kg / cm2. Based on the results of the compressive strength test shows that the compressive strength value obtained is increasing with increasing age of the treatment of the test specimens.